ANALISIS MAKNA MUBAARAK DALAM AL-QUR’AN - Kgs. M. Choirul Muchlis; Halimatussa’diyah (PT. Pustaka Cendekia Publisher, 2024)
Research with the title meaning of mubaarak in the Koran. This study is motivated by the fact that there are still many Muslims who misunderstand the meaning of the word mubaarak and its application in life. Therefore, the focus of discussion in this study is: 1. What does mubaarak mean in the Qur'an? 2. What is the analysis of the meaning of mubaarak in the Qur'an?. The type of research in this scientific work is library research (library) with research results that are based on data. The research method used is thematic (maudhu'i) with a qualitative approach using data analysis techniques (content analysis) and the theory used is semantic and social theory. The data sources used in this study are primary data sources, namely the Koran and secondary data, namely commentaries and relevant literature. The data collection technique is based on the thematic research method (maudhu'i), so that all verses meet at one mouth, without inappropriate differences and contradictions. After the data is collected then data analysis or small conclusions are carried out on each discussion. The results of this study using a semantic theory approach that mubaarak is God's goodness bestowed on an object, namely, the Qur'an. And the analysis of the meaning of mubaarak according to the commentators is a steady, full, abundant and growing goodness given by Allah for the object He wants, namely the Qur'an. However, there is a slight difference in terms of the style of interpretation, the classical interpretation is more inclined towards the bil ma'tsur interpretation, while the contemporary interpretation is more towards the bil ra'yi interpretation with the style of al-adabi wa al-ijtima'i. So that the word mubaarak explains that there is a goodness that comes from Allah to an object that is desired by Allah.